2023
DOI: 10.3389/fpsyg.2023.1132608
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity of the polish short form version of the self-regulated learning—sport practice survey among competitive athletes

Abstract: IntroductionSelf-regulated learning entails psychological processes that elite athletes employ to optimize their practice. Although self-regulated learning provides insights into athlete-led practice, research has been limited to few cultures, and the particularities of how SRL surveys perform in new cultural contexts require attention. Moreover, there exists no measure to assess SRL and its relationship to quality sport practice in Polish. Thus, we examined the Short Form of the Self-Regulated Learning—Sport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Outside of pilot work with applied consultants, initial insights into how the SRSP could be used in an applied context came in a Polish case study. Siekańska et al (2020) validated a shortform version of the SRL-SP in Polish and had an experienced SPC implement it in her discussions with a highly elite freediver. The athlete first completed the survey in reference to his current training experiences, and then reflected on how he may have responded as a sub-elite athlete six years earlier, before he implemented mental training into his practice.…”
Section: Developing the Construct Validity Of The Self-regulated Spor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of pilot work with applied consultants, initial insights into how the SRSP could be used in an applied context came in a Polish case study. Siekańska et al (2020) validated a shortform version of the SRL-SP in Polish and had an experienced SPC implement it in her discussions with a highly elite freediver. The athlete first completed the survey in reference to his current training experiences, and then reflected on how he may have responded as a sub-elite athlete six years earlier, before he implemented mental training into his practice.…”
Section: Developing the Construct Validity Of The Self-regulated Spor...mentioning
confidence: 99%
“…Post-practice, it had become easier for him to evaluate his weaknesses because he also learned to simultaneously seek information to evaluate strengths, which maintained his self-confidence. Siekańska et al (2020) concluded that the survey could inform fruitful discussion on how athletes manage their own learning via planning, monitoring, and corrective methods in training. They saw it as a useful dialogue tool for helping athletes develop proactive SRL approaches to their practice tasks.…”
Section: Developing the Construct Validity Of The Self-regulated Spor...mentioning
confidence: 99%